2017
DOI: 10.3329/jninb.v1i2.29850
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics and Etiology of Hydrocephalus Patients attended at Tertiary Care Hospital in Bangladesh

Abstract: Background: Hydrocephalous can occur at any age. Objectives: The purpose of the present study was to see the Demographic Characteristics and Etiology of Hydrocephalus Patients. Methodology: This cross sectional study was conducted in the Department of Neurosurgery at Bangabandhu Sheikh Mujib Medical University, Dhaka from April 2009 to September 2010 for a period of one and half year. Patients presented with obstructive hydrocephalus at any age with both sexes were included as study population. Detailed socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…This study included all the operated cases of VP shunt surgery admitted to the Institute of Medical Sciences, Banaras Hindu University, Varanasi, between October 2018 to January 2020. Male predominance was observed in this case series, which is similar to the observation of Milhorat 11 and Rahaman et al 12 Most patients in our study were from pediatrics and adolescent age group. In a meta-analysis by Issac et al, it is found that there is a U-shaped pattern across the age continuum in the prevalence of hydrocephalus, with an 8-fold decline from pediatrics to adults and a subsequent 17-fold rise to the elderly.…”
Section: Discussionsupporting
confidence: 92%
“…This study included all the operated cases of VP shunt surgery admitted to the Institute of Medical Sciences, Banaras Hindu University, Varanasi, between October 2018 to January 2020. Male predominance was observed in this case series, which is similar to the observation of Milhorat 11 and Rahaman et al 12 Most patients in our study were from pediatrics and adolescent age group. In a meta-analysis by Issac et al, it is found that there is a U-shaped pattern across the age continuum in the prevalence of hydrocephalus, with an 8-fold decline from pediatrics to adults and a subsequent 17-fold rise to the elderly.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies show similar results. [13][14][15] In present study enlargement of head, bulging of fontanelle, setting sun sign are the commonest presenting signs and symptoms. Similar type of presentation is seen in various other studies also.…”
Section: Resultssupporting
confidence: 49%
“…Similar type of presentation is seen in various other studies also. [8][9][10][11][12][13][14][15][16][17] Commonest cause of hydrocephalus in our study is Aqueductal stenosis (40%) followed by Arnold Chiari type 2 malformation (23.33%) with meningomyelocele. Similar aetiology is seen in various other studies also.…”
Section: Resultsmentioning
confidence: 99%